Engineering postgraduate colloquium, 2004 - Universiti Malaysia Sarawak, Faculty of Engineering (Universiti Malaysia Sarawak (UNIMAS), 2004)
Pictures of participate during Engineering Postgraduate Colloquium that has been chaired by Dr. Awangku Abdul Rahman Pengiran Hj Yusuf